(untitled) (Andamios, Revista de Investigación Social, 2010)
Some theoretical and clinical consequences emerge after Freud establishes an analogy between the psychic apparatus and a writing machine. In theoretical terms, when the psychic apparatus’ mechanism is a process of inscription, the memory trace is alterable. If the trace can be modified, memory is a phenomenon immersed within what Derrida calls hantology or ontology haunted by “ghosts” coming from the past and from the future and no an archive of past “presents.” Memory in Freud is then attuned with the Derridian understanding of the event since it comes out as repetition in difference, that is, since each “new” trace keeps something from the prior text while at the same time emerges as inauguration. Clinically, it shows necessary to abandon the search of an ultimate and original sense in the patient’s discourse.